IDENTIFICATION OF HONEY FROM THE ALTAI TERRITORY USING DIFFERENTIAL SCANNING CALORIMETRY AND THERMOMECHANICAL ANALYSIS - Vereshchagin A.L.; Bychin N.V.; Nagih A.A. (Техника и технология пищевых производств)
The samples of honey from the Smolensk region of the Altai territory (52°15' N. 85°08' E., 2013) were studied in the temperature range from -100°C to +70°C with differential scanning calorimetry using the Shimadzu-60 device (Japan, Shimadzu) and the thermo-mechanical analysis using the DMA 982 device connected with DuPont 1090 thermal analyzer (USA, DuPont) to determine the initial softening temperature applying the Wick’s method. The samples of mono-flora (Onobrychis) and poly-flora (Onobrychis+Melilotusofficinalis) honey, as well as processed sucrose and sucrose syrup have been studied. Organoleptic evaluation of samples for taste, smell, texture and color showed that all samples had a distinctive taste and smell of honey. To compare the samples, three different stages were defined: 1. (eutectic formation) from -20°C to +5°C; 2. (melting) from +5°C to +20°C; 3. (homogenization) from +20°C to +70°C. It has been established that the shape of the DSC curves, phase transition temperatures and the thermal effect depend on the origin of the samples, which provides ground for using the DSC method. The differences in the form of DSC curves, phase transition temperatures and thermal effect values have been determined depending on the sample origin. This result gives ground to use the DSC method to identify the origin of honey samples.